Experiences of family caregivers of persons living with mental illness: A meta-synthesis - Esther I. Ntsayagae; Marie Poggenpoel; Chris Myburgh (AOSIS, 2019)
Background: Meta-synthesis is used to generate and understand new insights from a qualitative perspective. Caregiving is associated with a range of physical and psychological symptoms. Caregivers bear the brunt of caregiving and this has become worse since the inception of de-institutionalisation, as more patients are discharged into the community under the care of their families. Objectives: The purpose of this study was to synthesise phenomenological qualitative studies and create a comprehensive chronicle of phenomena of family caregivers' experiences of caring for relatives living with mental illness. Method: Google Scholar and different electronic databases, which included CINAHL, MEDLINE, EBSCO and PubMed, were searched using keywords for relevant studies published from 1994 to 2014. To obtain an in-depth view of caregivers' lived experiences, a qualitative meta-synthesis was employed to review the findings of 10 studies. Results: A total of 10 studies were included in the meta-synthesis. The family caregivers described their caregiving experiences under four themes: perceived responsibility of caregiving, experiences of emotional effect, experiences of support needs and experiences of changed perspective. Conclusion: The meta-synthesis revealed a lack of emotional coping among the family caregivers. This calls for robust family caregiver interventions to facilitate their mental health.